Human Immunodeficiency Virus (HIV)– and Non-HIV–Associated Immunosuppression and Risk of Cervical Neoplasia. Issue 1 (January 2018) - Silverberg, Michael J.; Leyden, Wendy A.; Chi, Aileen; Gregorich, Steven; Huchko, Megan J.; Kulasingam, Shalini; Kuppermann, Miriam; Seto, Anna; Smith-McCune, Karen K.; Sawaya, George F.
Abstract : OBJECTIVE: To estimate the risk of cervical intraepithelial neoplasia grade 2, 2–3, 3, adenocarcinoma in situ, or cancer (CIN 2 or worse) among women with human immunodeficiency virus (HIV)– and non-HIV–associated immunosuppression. METHODS: We performed a case–control study of 20, 146 women with incident CIN 2 or worse and 5:1 age-matched, incidence-density selected women in a control group (n=100, 144) enrolled in an integrated health care system from 1996 to 2014. Adjusted rate ratios (RRs) from conditional logistic regression were obtained for HIV status (stratified by CD4 + T-cells), solid organ transplant history, and immunosuppressive medication use. RESULTS: Risk of CIN 2 or worse was increased among women with HIV (n=36 women in the case group and 79 women in the control group; adjusted RR 2.0, 95% CI 1.3–3.0) compared with those without HIV and in solid organ transplant recipients (n=51 women in the case group and 68 women in the control group; RR 3.3, 95% CI 2.3–4.8) compared with women without a prior transplant. The highest risks were among women with HIV and less than 200 CD4 + T-cells/microliter (n=9 women in the case group and eight women in the control group; RR 5.6, 95% CI 2.1–14.7) compared with those without HIV and in solid organ transplant recipients prescribed three or greater immunosuppressive medication classes (n=32 women in the case group and 33 women in the control group; RR 4.1, 95% CI 2.5–6.8) compared with women without a prior transplant and zero medication classes. No increased risks were observed for women with HIV and 500 or greater CD4 + T-cells/microliter (n=9 women in the case group and 43 women in the control group; RR 0.8, 95% CI 0.4–1.7) compared with those without HIV or women without prior solid organ transplantation prescribed two or fewer immunosuppressive medication classes (n=1, 262 women in the case group and 6, 100 women in the control group; RR 0.95, 95% CI 0.89–1.01) compared with women without and a prior transplant and zero medication classes. CONCLUSION: Risk of CIN 2 or worse is increased in women with a prior solid organ transplant or who have HIV and CD4 + cells/microliter less than 500 but not in women with HIV and higher CD4 + levels or in women without a prior solid organ transplant but who are prescribed only one or two immunosuppressive medication classes. Abstract : Cervical neoplasia risk is not increased in women with human immunodeficiency virus with high CD4 + counts or in women without solid organ transplantation prescribed two or fewer immunosuppressive medication classes.